Highly efficient photocatalytic activity and mechanism of Yb3+/Tm3+ codoped In2S3 from ultraviolet to near infrared light towards chromium (VI) reduction and rhodamine B oxydative degradation - Wu, Zhibin (2020)
The Yb3+/Tm3+ codoped flower−like tetragonal In2S3 photocatalysts were synthesized through a hydrothermal route, and the crystal phases, morphologies, chemical compositions and optical properties were characterized. The results shown that the doping with Yb3+/Tm3+ did not significantly change the crystallinity of In2S3, but induced the generation of intermediate energy states for efficient charge separation. The Yb3+/Tm3+ codoped In2S3 presented a significant enhancement of photoactivity towards chromium (VI) reduction and rhodamine B oxidation from UV to NIR light. The best photocatalytic synergism was obtained for the sample with the mole ratio of In3+:Yb3+:Tm3+ at 159:40:1, in which the chromium (VI) reduction efficiency was 97.9% (NIR, 100 min), 99.3% (vis, 10 min) and 98.3% (UV, 10 min), while the rhodamine B degradation efficiency was 98.4% (NIR, 100 min), 97.3% (vis, 14 min), and 96.3% (UV, 14 min). The favorable NIR photoactivity was mainly attributed to the upconversion mechanism via energy level transition of Yb3+/Tm3+. Under the full−spectra−light irradiation for 6 min and 7 min, the removal efficiency of chromium (VI) and rhodamine B could reach to 99.4% and 94.8%, the corresponding rate constant was 2.17 and 5.60 times of pure In2S3, respectively. The improved photocatalytic efficiency might be attributed to the enhanced light absorption and favorable charge separation resulted from the intermediate energy states and/or sulfur vacancies. In addition, the free radical capture and electron spin resonance experiments were also performed to determined the role of [rad]O2− and h+ species during photocatalytic oxidation process.